2017
DOI: 10.3390/app7080813
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Control of Wastewater Treatment Plants Using Economic-Oriented Model Predictive Dynamic Strategies

Abstract: This paper addresses the implementation of economic-oriented model predictive controllers for the dynamic real-time optimization of the operation of wastewater treatment plants (WWTP). Both the economic-optimizing controller (pure-EMPC) and the economic-oriented tracking controller (Hybrid-EMPC, or HEMPC) formulations are validated in the benchmark simulation model (BSM1) platform that represents the behavior of a characteristic activated sludge process. The objective of the controllers is to ensure the approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 25 publications
(29 reference statements)
0
35
0
1
Order By: Relevance
“…Different control strategies to improve the operation of WWTPs have been proposed in a significant number of works ( [12][13][14][15][16][17][18], but the evaluation of performance and the optimization objectives, in the case of optimizing control strategies ( [15][16][17][18]), concerns the quality of the effluent and economic aspects. Since pollution removal takes place in the activated sludge process (ASP) in the water line, the control strategies are applied to regulate dissolved oxygen (DO) in the aerobic zone or ammonium concentration in the effluent through manipulation of aeration intensity, and nitrates concentration in the anoxic zone.…”
Section: Introductionmentioning
confidence: 99%
“…Different control strategies to improve the operation of WWTPs have been proposed in a significant number of works ( [12][13][14][15][16][17][18], but the evaluation of performance and the optimization objectives, in the case of optimizing control strategies ( [15][16][17][18]), concerns the quality of the effluent and economic aspects. Since pollution removal takes place in the activated sludge process (ASP) in the water line, the control strategies are applied to regulate dissolved oxygen (DO) in the aerobic zone or ammonium concentration in the effluent through manipulation of aeration intensity, and nitrates concentration in the anoxic zone.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, all measured data can be reported as daily, monthly or yearly averages, being 3 years the recommended time period for data gathering to account for seasonal variability associated with the human activities and the seasonal rainfall. Due to the variable influent behaviour, the pollution load to be treated is continuously changing, and consequently, so are the energy and chemical requirements for the treatment [33]. To sum up the procedures, first the type of WWTP is established according to its functions; then, energy consumption and other measurements (flowrate, pollutant concentrations, etc.)…”
mentioning
confidence: 99%
“…1 (BSM1) is selected to represent the activated sludge process, and this is a recognized benchmark plant designed for the evaluation of different control methodologies. There are many applications of centralized linear and nonlinear MPC strategies to WWTP control, some of them in a hierarchical framework [18][19][20][21][22]. However, to the authors' knowledge, no collaborative control applications to WWTP have been found in the literature.…”
Section: Introductionmentioning
confidence: 99%